State of gata2 Gene in Hematopoietic Stem Cells Of Recipients With Graft Versus Host Disease Induced by Cryopreserved Allogeneic Material - Goltsev, Anatoliy N.; Dubrava, Tatyana G.; Gaevskaya, Yuliya A.; Lutsenko, Elena D.; Ostankov, Maksim V. (Problems of Cryobiology and Cryomedicine, 2015)
A significant problem of transplantation of histoincompatible bone marrow (BM) is the development of an immune conflict, which is clinically manifested as the graft-versus-host disease (GVHD). This paper concerns the state of hematopoietic system in animals under conditions of experimentally induced GVHD. The pathology was induced by introduction of either native or cryopreserved allogeneic BM jointly with lymph node cells. The rate of gata2 gene expression was examined in hematopoietic stem cells (HSCs) of BMs from the recipients with GVHD. Methods of cryopreservation, immune fluorescence, and RT-PCR were used in the research. Bone marow cells exhibited an increased expression of gata2 gene, responsible for self-maintenance of HSCs, as well as changed subpopulation composition, that could lead to the reduction of the medullary haematopoiesis in GVHD animals. In the group of animals with GVHD, induced by allogeneic cryopreserved BM with a high level of gata2 gene expression, a low rate of medullary haematopoiesis was found. This fact emphasizes the importance of inhibitory effect rendered by cryopreservation in terms of functional status of the HSCs, which is manifested in this case as the decrease of their differentiation potential and recovery of medullary haematopoiesis. The performed studies expand our understanding about the mechanisms of GVHD at cell and molecular levels, which may prove the expediency of the directed elevation of efficiency in the treatment of one of autoimmune pathologies. Probl Cryobiol Cryomed 2015; 25(1):67-75.